UPAYA MENINGKATKAN HASIL BELAJAR SISWA TEMA 7 SUBTEMA 2 INDAHNYA KERAGAMAN BUDAYA NEGERIKU MENGGUNAKAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING KELAS IV SD NEGERI 100670 HUTAIMBARU T.A 2021/2022 - hazza nur husnipa harahap; Nurbaiti Nurbaiti; Monica Theresia (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2023)
Abstract This study aims to improve learning outcomes of theme 7 sub-theme 2 the beauty of cultural diversity in my country using the Contextual Teaching and Learning (CTL) learning model for class IV SD 100670 Hutaimbaru T.A 2021/2022. This research is a classroom action research (CAR). Which is carried out in cycle II. Data collection techniques used are teacher observation sheets and test questions. The application of the Contextual Teaching and Learning (CTL) model can improve learning outcomes 7 sub-theme 2 The beauty of my country's cultural diversity. The results of my cycle show the results of observations from learning activities of 67.30% (enough category) and the average student learning outcomes are 67.55% where 6 students (30%) are complete and 14 students (70%) are not. . Furthermore, the second cycle showed the results of observation of learning activities of 80.76% (high category) and an average of 78.05% where 16 students (70%) completed and 4 students (30%) did not complete. It can be concluded that student learning outcomes in theme 7 sub-theme 2 are the beauty of my country's cultural diversity using the Contextual Teaching and Learning (CTL) learning model for class IV SD 100670 Hutaimbaru T.A 2021/2022 Keywords: Improved Learning Outcomes, Contextual Teaching and Learning (CTL) Model